Going home? Exiles, inciles and refugees in the Book of Jeremiah - Claassens, L. Juliana M. (HTS teologiese studies, 2019)
Set against the backdrop of the Babylonian Invasion and Exile, the Book of Jeremiah represents a variety of different perspectives on how to survive imperial domination. This article explores three competing visions that can be described in terms of the tension that exists between the pro-golah group that propagated life in Babylon, the anti-golah group that saw the hope for the future back home and the group of refugees who in the aftermath of the Mizpah massacre found themselves fleeing to Egypt. In the current context of global migration, this article considers theological and ethical perspectives generated by the engagement with Jeremiah on home and homecoming in a context where there is no good option.